SISTEM ESTIMASI SIGNAL TO NOISE RATIO UNTUK KOMUNIKASI DATA DARI ROBOT (OMNIWEEL) KE ANDROID DENGAN MENGGUNAKAN METODE KORELASI - Setiawan, Deni; Syafaat, Mokhamad; Setiawan, Arif (Pustaka Poltekad, 2020)
The design of a surveillance robot control system can be controlled by an android smartphone via a wi-fi wireless network. The robot is equipped with a hidden camera to obtain enemy target data in the form of video in real-time around the robot and then displayed on the android smartphone application. Robots made are like cars in the shape of an Omni wheel can move in any direction. Communications are made using a wifi wireless device on the android smartphone for two-way communication sending and receiving data between the android smartphone and the raspberry PI on the surveillance robot. The data obtained are sent using a system of estimation signal to noise ratio from the surveillance robot (Omni wheel) to android for maximizing of data communication from surveillance robot (Omni wheel) to android using correlated methods. Because this robot can be controlled by android so it is suitable for surveillance to reduce personnel risks directly.